(untitled) - FAO (Rome, Italy, 1996)
This book contains five thematic areas: assessment and monitoring of non-timber forest products; indigenous knowledge and ethnobotany; product development and management; product domestication and adoptions by farmers; and policies and institutional aspects
Keywords: forest products,forests and forestry - economic aspects